Wood Chip Incorporation in Almond Orchard Planting Berms Increased Gravimetric Water Content, Soil CO2 Efflux, and Fine Root Length Density - Hana You; Paul Martinez; Mae Culumber; Brent Holtz; Astrid Volder (HortScience)
Incorporation of chipped woody material into soil instead of burning or transporting wood chips (WCs) off-site is a practical solution to dispose of old orchard trees. In woody plants, the most external (fine) lateral roots are critical in acquiring water and nutrients and are the part of the root system that is most responsive to changes in the soil environment. Our objective was to measure the impact of pre-planting WC incorporation into the planting site on young almond tree root parameters such as root length density (root length per soil volume) and root architecture. We hypothesized that presence of decomposing WCs in soils in the years following planting leads to increased fine root length density and changes in root architecture that increase soil exploration per unit root biomass. Plum WCs were incorporated into the orchard soil 6 months before planting and three blocks were established with paired treatment and control (no WC) plots. Root traits, soil water content, soil bulk density, and soil CO2 efflux were measured in both the berm and alleyways twice in years 2 and 3 after planting. We found significant increases in standing root length density in planting berms with WC incorporation 2 and 3 years after trees were planted. This was due to an increase in root mass per soil volume rather than an increase in specific root length or a change in proportion of fine roots produced. Thus, although root foraging was increased in planting berms with WCs incorporated, this was not due to a change in root architectural traits.